Distinct microbiota assembly and functional patterns in disease-resistant and susceptible varieties of tobacco - Yang, Luhua; Guo, Yuan; Yang, Hui; Li, Shun; Zhang, Yunzeng; Gao, Cheng; Wei, Tian; Hao, Likai (Frontiers in Microbiology, 2024)
Plant microbiota is believed to be an accessory genome extending plant functions, forming holobiont together with the host plant. Plant disease resistance, therefore, is inextricably linked with plant microbiota, which play important roles in plant growth and health. In order to explore the relationship between plant microbiota and disease resistance, we investigated the tobacco microbiome of two varieties with contrasting disease resistance levels to bacterial wilt and black shank. Comparative microbiome analysis indicated that the resistant variety assembled a distinct microbiota with higher network complexity and diversity. While Pseudomonas and Ensifer, that contain biocontrol and beneficial members, were enriched in the rhizosphere of the resistant variety, Ralstonia, a genus including the known causative pathogen, was enriched in the susceptible variety. Metagenome sequencing revealed that biocontrol functions were more abundant in the resistant variety, such as hydrogen cyanide synthase, pyochelin biosynthesis, and arthrofactin-type cyclic lipopeptide synthetase. Further analysis indicated that contigs encoding the corresponding genes were mostly assigned to Pseudomonas. Among all the metagenome-assembled-genomes, positive selection was suggested in the genome assigned to Pseudomonas only in the rhizosphere of the resistant variety. The search of biosynthetic gene clusters in the Pseudomonas genome revealed a nonribosomal peptide synthetase, the compound of which was brabantamide A, with known antimicrobial activity. Collectively, our study suggests that the plant microbiota might be involved in the microbe-mediated disease resistance. Particularly, our results highlight Pseudomonas in the rhizosphere of the disease-resistant variety as the promising biocontrol candidate. Our study may facilitate further screening of bacterial isolates and the targeted design of microbial communities.